(untitled) (Research, Society and Development, 2022)
The present work aims to understand how was the insertion of the social worker in public health policy, where it will analyze the trajectory of the Unified Health System and the difficulties and obstacles that the social service professional had when entering this area. Seeking every day to face a review process in professional training brought to a discussion of health work. The research is a study carried out through an integrative literature review. We used the Virtual Health Library (VHL), Latin American and Caribbean Health Sciences Literature (LILACS) and Medical Literature Analysis and Retrievel System Online (MEDLINE) databases, as well as the Scientific Electronic Library database. Online (SCIELO). The descriptors of science will address the Social Worker and Public Health, considering its disciplinary particularity in health and the reconstruction of the object privileging the formative aspect. In this context, far from offering conclusive results, we intend to encourage critical reflection on the nuances and mishaps that the social worker goes through to reduce the bureaucracy of the demands placed on health for this professional.